The importance of first aid in the story «Hilachas» - Idrogo Benavides, Gabriela Suley (2022)
This article will deal with the story «Hilachas», by Ricardo Palma, specifically chapter IV, entitled «Lapsus linguae episcopal». In this text, an event occurs in which by chance a person is saved by performing a first-aid technique. From this, it is proposed to analyze the importance of every citizen, especially health professionals, knowing how to apply first aid in an emergency. It will also detail what the first aid kit consists of and what are the most common emergency cases.